O tempo afrofuturista: outras formas de conceber realidades de coloniais - Santos, Nathalya Victoria Lima dos (2024)
This research proposes an investigation into Afrofuturism and its diverse fables, exploring its connections with cultural representations surrounding the black body in modernity. Through analyses of Afrofuturist musical, visual, and literary works and through the lens of Afrofuturism, this dissertation aims to explore singularities that challenge linear perspectives of time, body, and history. The intention is to construct a subaltern perspective that remains outside the scope of official history, impacting various social groups affected by colonial processes. In doing so, there are no boundaries perceived between art and black existence (body), and the research seeks, through cultural practices, to contest conceptions of futures against prevailing colonial systems and their ramifications rooted in the present. These counter-futures generate new temporalities by fabulating unofficial histories, employing non-linear concepts of time that are overlapping, cyclical, multiversal, and parallel, depending on the assumed universe. The focus of this research is to understand how these imaginaries are predominantly developed within culture and how languages, expressed through visual and auditory elements, performance, in a synesthetic ensemble, engage with concepts of orality in maintaining a perspective systematically marginalized, non-linear, and corporeal. Considering that colonial methodologies contribute to stigmatized perspectives of the black population, movements like Afrofuturism propose a new temporal conception that can be interpreted on its own terms. Thus, adopting a decolonial approach, this text seeks to present Afrofuturism as a perspective and one of the possibilities for interpreting the record of black history in time and its forms in the struggle for a representation aligned with a pluralistic history